Experience in using secukinumab in patients with axial psoriatic arthritis - E. E. Gubar; Yu. L. Korsakova; E. Yu. Loginova; T. V. Korotaeva (Современная ревматология, 2020)
Axial skeletal injury is observed in 25–70% of patients with psoriatic arthritis (PsA). Spondylitis frequently occurs subclinically, which leads to serious structural and functional disorders over time. An update shows that axial skeleton involvement in PsA is characterized by a more severe clinical course: these patients are observed to have a greater severity of peripheral arthritis, enthesitis, and dactylitis, skin and nail psoriasis, a higher CRP level, and worse functional status. In addition, the disease is more severe according to the patients' subjective assessment, as evidenced by questionnaires. Synthetic disease-modifying antirheumatic drugs used to treat peripheral PsA are not recommended for axial injury. When nonsteroidal anti-inflammatory drugs are ineffective, biological drugs (tumor necrosis factor-α inhibitors or interleukin-17A (IL-17A) inhibitors) should be prescribed immediately to patients with psoriatic spondylitis. The paper describes two clinical cases demonstrating the successful use of the IL-17A inhibitor secukinumab (SEC) in patients with axial PsA (axPsA). Given the positive experience with SEC in real clinical practice, it seems reasonable to prescribe it to patients at earlier stages of axPsA.